Transplantation of cardiac Sca-1-positive cells rather than c-Kit-positive cells preserves mitochondrial oxygen consumption of the viable myocardium following myocardial infarction in rats - Tetsuro Marunouchi; Kyohei Sasaki; Emi Yano; Kouichi Tanonaka (Elsevier, 2019)
The cardiosphere-derived cell (CDC) is one of the candidate cells used for cardiac regenerative therapy. Cardiospheres are mixture of cells including c-Kit+ cells, stem cell antigen (Sca)-1+ cells, and other types of cardiac progenitor cells. In this study, we compared the effect of transplantation of isolated Sca-1+ cells and c-Kit+ cells with that of the crude CDCs (CrCDCs). Focusing on the differences in the ability for secretion of paracrine factors among 3 types of cells, we determined the effects of transplantation of these cells on cardiac intracellular signaling and mitochondrial function in rats with permanently ligated coronary arteries. We showed that the transplantation of these cells resulted in a preservation of the cardiac pump function and mitochondrial respiration at the 8th week after myocardial infarction. However, mitochondrial function in the c-Kit+ cell-transplanted group was lower than that in the other 2 groups. Furthermore, we found that activation levels of intracellular signaling proteins after cell transplantation may have been due to the ability of secretion of growth factors by these transplanted cell types. Our findings indicate the possibility that CrCDC and Sca-1+ cells rather than c-Kit+ cells may be used therapeutically to preserve cardiac function and energy metabolism after myocardial infarction. Keywords: Mitochondria, Heart failure, Cell transplantation, Sca-1, c-Kit